2019
DOI: 10.1111/nhs.12595
|View full text |Cite
|
Sign up to set email alerts
|

Effect of peer support on health outcomes in patients with cardiac pacemaker implantation: A randomized, controlled trial

Abstract: The aim of this study was to examine the effect of a nurse‐led telephone‐based peer support program on health outcomes in patients after cardiac pacemaker implantation. Seventy six patients who received cardiac pacemaker implantation were recruited as participants and randomly assigned to either the peer support group or the usual care group. The usual care group received routine care and health education measures provided by nurses; the peer support group received telephone‐based peer support. Health‐related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…The aim is to avoid complications (dislocation of electrodes, pocket injury). 14 However, after L‐PM implantation, the patient only needs to press the femoral vein of the affected side for 6 h, and there is no subsequent braking requirement. These all cause discomfort and mood swings in patients with C‐PM, and thus may explain the differences in physical health that we found at 1‐ and 3‐month follow‐up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The aim is to avoid complications (dislocation of electrodes, pocket injury). 14 However, after L‐PM implantation, the patient only needs to press the femoral vein of the affected side for 6 h, and there is no subsequent braking requirement. These all cause discomfort and mood swings in patients with C‐PM, and thus may explain the differences in physical health that we found at 1‐ and 3‐month follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…This study shown that patients in the L-PM group had more significant improvements in physical health, higher scores in PF and RP, and less discomfort in surgical area and restricted mobility due to The aim is to avoid complications (dislocation of electrodes, pocket injury). 14 However, after L-PM implantation, the patient only needs to press the femoral vein of the affected side for 6 h, and there is no subsequent braking requirement. These all cause discomfort and mood swings in patients with C-PM, and thus may explain the differences in physical health that we found at 1-and 3-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing data indicate that adult patients with implantable cardiac devices, such as PM and implantable cardioverter-defibrillator, frequently report on symptoms of depression and anxiety [ 2 , 3 ]. For example, the mean baseline scores on the depression and anxiety subscales of the Hospital Anxiety and Depression Scale in a Chinese intervention study indicate that self-reported symptom levels of depression and anxiety among PM recipients are well above those reported in community-based samples [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Não foi identificado diferença após essa intervenção nos desfechos de ansiedade e depressão analisados pelo HADS. 72 Rosic et al, avaliou os efeitos de programas educacionais, de aconselhamento, e terapias comportamentais sobre os aspectos de ansiedade, depressão e QdV de pacientes com diversas cardiopatias. Os mesmos foram aplicados em uma população caracterizada pelo sedentarismo, obesidade, sintomas de ansiedade e depressão.…”
Section: Discussionunclassified